Melqart, Hercules Gaditanus and Híppos of Hadrian Aurei. - Mora-Serrano, Bartolomé (Consiglio Nazionale delle Ricerche, 2023)
Worth highlighting among the depictions on the reverses of Hadrian aurei dedicated to different divinities are those of Hercules Gaditanus. These representations combining a victorious image of the Emperor depicted as a god with what was the fictitious limit of the known world are charged with potent symbolism. This study focuses on aurei (RIC II/3 572-578 and 555) bearing the image of Oceanus accompanied by a ship’s prow marked by a distinct adornment. Apart from the more basic reading of this detail that reinforces the well-known oceanic vocation of Gadir/Gades, this study delves into the possibility of interpreting the scene from a Hispano-Phoenician viewpoint linked to the key role played by the iconography of the ship. The ship/híppos represents a key element in the Phoenician-Punic imaginary with a bond to the god from Cadiz, whose likeness can be traced through this Roman coinage which was especially beloved by the emperors of Hispanic origin.
Keywords: Numismática romana; Hercules Gaditanus; Melqart; Gadir-Gades; Hippos; Adriano; Aurei